KAJIAN INTERTEKS NOVEL LAYAR TERKEMBANG KARYA SUTAN TAKDIR ALISYAHBANA DAN NOVEL BELENGGU KARYA AMRIN PANE - Syamsidar, Raja (Jurnal Ilmu Budaya, 2010)
This writing aims to get objective description about intelectual relation between Sutan Takdir Alisyahbana's 'Layar Terkembang' and Amrin Pane's 'Belenggu'.